(untitled) (Symposium on Natural and Applied Sciences, 2026)
This article analyzes the theoretical foundations of developing a technological culture in the pedagogical process, the methodology for its improvement, and the effective use of modern educational technologies. It also examines ways to develop the technological competencies of teachers and students in the educational process.